Non-nutritive functional agents in rattan-shoots, a food consumed by native people in the Philippines. - Yu, G. B. (Compendium of Human Ecology Researches in the Philippines, 2003)
The tender shoots of Calamus ornatus, one of the food items consumed by the native people, Kanawan Aytas, in the Bataan region of the Philippines, have not been studied before. A bioassay-guided investigation of its methanjolic extract afforded non-nutritive functional agents (NFAs), steroidal saponins 1-3, along with its aglycone (4). The NFAs 1-4 inhibited cyclooxygenase enzymes, COX-1 and -2, by 47%, 43%, 33%, and 53% and 71%, 75%, 78%, and 73%,respectively at 28.2, 24.2, 21.2 and 60.4 μM. Treatment of breast (MCF-7), CNS (SF-268), lung (NCI-H460), colon (HCT-116) and gastric (AGS) cancer cell lines with the extract at 100μg/ml reduced cell proliferation. Similarly, the pure NFAs 2 and 3 reduced the cell viability of the breast, CNS, lung, colon and gastric cancer cell lines by 37.5%, 22.4%, 53.3%, 58.2%, 40.3% and 29.8%, 21.3%, 45.6%, 37.1%, 25.0%, respectively, at 24.2 and 21.2 M. The 50% reduction in cell viability (IC50) concentrations of 2 and 3 against these cancer cell lines were 8.8, 6.1, 7.5, 23.8, 12.1 and 3.8,7.1, 3.3, 12.3, 12.1 μM, respectively. This is the first report on the isolation of steroidal saponins from C. ornatus shoots and their anti-inflammatory and tumor cell proliferation inhibitory activities, thereby suggesting that the Kanawan Aytasmay yield health benefits from rattan-shoots in their diet.